Advances in concrete materials for sewer systems affected by microbial induced concrete corrosion: A review. (1st May 2018) - Grengg, Cyrill; Mittermayr, Florian; Ukrainczyk, Neven; Koraimann, Günther; Kienesberger, Sabine; Dietzel, Martin
Abstract: Microbial induced concrete corrosion (MICC) is recognized as one of the main degradation mechanisms of subsurface infrastructure worldwide, raising the demand for sustainable construction materials in corrosive environments. This review aims to summarize the key research progress acquired during the last decade regarding the understanding of MICC reaction mechanisms and the development of durable materials from an interdisciplinary perspective. Special focus was laid on aspects governing concrete - micoorganisms interaction since being the central process steering biogenic acid corrosion. The insufficient knowledge regarding the latter is proposed as a central reason for insufficient progress in tailored material development for aggressive wastewater systems. To date no cement-based material exists, suitable to withstand the aggressive conditions related to MICC over its entire service life. Research is in particular needed on the impact of physiochemical material parameters on microbial community structure, growth characteristics and limitations within individual concrete speciation. Herein an interdisciplinary approach is presented by combining results from material sciences, microbiology, mineralogy and hydrochemistry to stimulate the development of novel and sustainable materials and mitigation strategies for MICC. For instance, the application of antibacteriostatic agents is introduced as an effective instrument to limit microbial growth on concrete surfaces in aggressive sewer environments. Additionally, geopolymer concretes are introduced as highly resistent in acid environments, thus representing a possible green alternative to conventional cement-based construction materials. Graphical abstract: Image 1 Highlights: Key research progress regarding microbial induced concrete corrosion (MICC). Mechanisms steering concrete – microorganism interaction in MICC environments. Impact of physiochemical concrete parameters on microbial community structures. Possible application of antibacteriostatic agents in aggressive sewer environments. Advantages of geopolymer technology for applications in MICC environments.